A história da matemática no ensino da geometria: uma contextualização pela razão áurea - Linck, Leandro Alex (2017)
The present work intends to extend the knowledge about a very interesting and instigating theme that is the Golden Ratio, to recover its history and its importance mainly within Geometry, to argue about the importance of this Ratio in the construction of mathematical knowledge, identifying the possible connections with geometry and the most different areas of knowledge. Not leaving aside the survey on the History of Mathematics as a form of teaching methodology, because one has the awareness that every teaching process should be based on its history, and could not be different in Mathematics. Also perform a survey on what are the guidelines of the National Curricular Parameters and the Curriculum of the State of São Paulo for the teaching of Geometry and from this information to develop activities involving the Golden Ratio and Geometry, aiming to lead the student through different activities, to build their mathematical knowledge. The five activities proposed in this work were designed in such a way as to be interdisciplinary in order to show students that mathematics can be applied in several areas of knowledge that make use of Geometry and thus propose the following research question: "What contributions do the history of mathematics contextualized by golden reason can bring to the teaching of geometry?" This is a bibliographic review research. The analysis carried out regarding the teaching of geometry presupposes that many are the contributions in the different school series, presented by the contextualization of Mathematics with the use of the Golden Ratio. The study carried out through the contextualization can awaken in the student a greater motivation, since they can relate everyday situations to the theory learned in the classroom, and consequently helps in the construction of knowledge.